Synthesis of Ba0.5Sr0.5(Ti0.80Sn0.20)O-3 prepared by the soft chemical method - Souza, I. A.; Simoes, A. Z.; Longo, Elson [UNESP]; Varela, José Arana [UNESP] (Elsevier B.V., 2007)
Single-phase Ba0.5Sr0.5(Ti0.80Sn0.20)O-3 (BST:Sn) powders with perovskite structure were prepared by the soft chemical method. Infrared data indicates that the BST:Sn powder is carbonate free while Raman analysis has shown that the transversal (TO) and longitudinal (LO) optical modes tend to disappear with tin addition. The electron diffraction pattern of the BST:Sn powder showed an interplanar distance of 3.94 angstrom characteristic of the pseudo-cubic structure. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: chemical syntheses; X-ray technique; BST : Sn powders